Design, Development and Evaluation of Rivaroxaban Oral Films for Optimized Drug Delivery - Rama Rao Nadendla; Sandeep Kanna; Juluri Satyanarayan (Pharmaceutical Science: New Insights and Developments Vol. 2, 2025)
The COVID-19 pandemic has heightened the risk of thrombotic events, both microvascular and macrovascular, due to a hypercoagulable state triggered by inflammatory responses, endothelial dysfunction, and platelet activation in infected individuals. As a result, anticoagulants like Rivaroxaban (RN), a direct oral anticoagulant (DOAC) that inhibits Factor Xa and prevents clot formation, have been crucial in mitigating thrombotic risks. Rivaroxaban is commonly used in the treatment of venous thromboembolism, including deep vein thrombosis (DVT), and arterial thrombotic diseases like coronary artery disease (CAD) and peripheral artery disease (PAD). However, conventional tablet forms pose challenges for patients with dysphagia or difficulty swallowing, necessitating alternative drug delivery methods. This study aimed to develop fast-disintegrating Oral Thin Films (OTFs) of Rivaroxaban to address these challenges by improving bioavailability, enhancing patient compliance, and ensuring rapid drug release. OTFs dissolve quickly in saliva, making them ideal for patients with swallowing difficulties. Using the solvent casting method, the formulation incorporated super-disintegrants to ensure rapid disintegration and enhanced drug release. A 2² factorial design using Design-Expert® software has optimized critical formulation parameters such as super-disintegrant concentration and polymer composition. The optimized OTF exhibited rapid disintegration, with a cumulative drug release of 93.47% within 60 seconds. Short-term stability studies confirmed the formulations’ integrity under storage conditions. In vitro drug release followed first-order kinetics was primarily governed by Fickian diffusion, ensuring predictable drug delivery. The study demonstrates that Rivaroxaban OTFs offer a promising alternative to conventional dosage forms, improving bioavailability and patient adherence, particularly for those with swallowing difficulties or requiring rapid drug action. This innovative drug delivery system represents a significant advancement in anticoagulant therapy, with the potential for enhanced therapeutic outcomes.